2020
DOI: 10.3389/fphar.2020.01237
|View full text |Cite
|
Sign up to set email alerts
|

Urine Metabolomics Study on Potential Hepatoxic Biomarkers Identification in Rats Induced by Aurantio-Obtusin

Abstract: Previous studies revealed the hepatotoxic effect of aurantio-obtusin on rats. The aim of this study was to identify potential biomarkers of urine caused by aurantio-obtusin. Sprague–Dawley (SD) rats with body weight of 0, 4, 40, and 200 mg/kg were orally given aurantio-obtusin for 28 days, and urine was collected for 24 h after the last administration. The urine metabolites in the aurantio-obtusin group and the control group were analyzed by ultraperformance liquid chromatography quadrupole time-of-flight mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…We observed a significant increase in the histidine degradation pathway in Group A. Previous studies suggested that hepatic injury might be related to metabolic disorders in tryptophan metabolism and that pyrimidine metabolism disorders are associated with cellular liver damage (54,55). All of these previous reports are consistent with the findings of our research.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a significant increase in the histidine degradation pathway in Group A. Previous studies suggested that hepatic injury might be related to metabolic disorders in tryptophan metabolism and that pyrimidine metabolism disorders are associated with cellular liver damage (54,55). All of these previous reports are consistent with the findings of our research.…”
Section: Discussionsupporting
confidence: 93%
“…The metabolite 5-L-Glutamyl-taurineis, an intermediate in Taurine and hypotaurine metabolism, was significantly and positively correlated with all HF-related indices. Meanwhile, its increase is associated with hyperlipidemia ( Zeng et al, 2020 ), and aurantio-obtusin-induced hepatotoxicity ( Xu et al, 2020 ). The study carried out by Luo, Xiaomin et al showed that the therapeutic efficacy of Phyllanthus emblica aqueous extract on HF in NAFLD may be related to Taurine and hypotaurine metabolism ( Luo, et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the microbial tryptophan metabolites indole and 3-methyldioxyindole were decreased in the BG group. 3-methyldioxyindole is an oxidation product of 3-methylindole (also called skatole) in vivo ( Xu et al, 2020 ). Skatole is most probably a product in the colon and has been found to have a damaging effect on intestinal epithelial tissue activity and function after absorption but before detoxification ( Yokoyama and Carlson, 1979 ).…”
Section: Discussionmentioning
confidence: 99%